Innovation offshoring with fully endogenous growth - Colin R. Davis; Ken-ichi Hashimoto (Osaka University, Institute of Social and Economic Research (ISER), 2019)
In recent years firms have started to offshore their innovation activities to emerging economies. This paper investigates the implications of innovation offshoring for productivity growth in a two-country framework that features a tension between access to technical knowledge and low-cost high-skilled labor in the innovation location decision. Industry and innovation tend to concentrate in the asset-wealthy country when trade costs are relatively high. A positive relationship between innovation costs and industry concentration then ensures that improved international knowledge diffusion coincides with an increase in net offshoring flows in innovation from the asset-wealthy country to the asset-poor country, and potentially with faster productivity growth.
Keywords: F12; F43; R11; 330; innovation offshoring; international knowledge diffusion; endogenous productivity growth; process innovation; industry location; international trade